The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1007/bf01788904
|View full text |Cite
|
Sign up to set email alerts
|

Increased responsiveness to glucoregulatory effect of opiates in obese-diabetic ob/ob mice

Abstract: Plasma glucose and insulin responses to opiate receptor stimulation and antagonism were determined in 12-14 week old lean and obese-diabetic Aston ob/ob mice. The opiate receptor antagonist naloxone (1 mg/kg intraperitoneally) rapidly and transiently raised glucose and suppressed insulin concentrations in lean mice, and produced qualitatively similar but more protracted response in ob/ob mice. Selective stimulation of mu- and delta-opiate receptors using the enkephalin analogues Tyr-D-Ala-Gly-MePhe-NH(CH2)2OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…Obese mice were also hyperglycaemic and hyperinsulinaemic as compared with lean mice (Fig. 1c and Table 2) [31]. All these parameters remained rather stable throughout the 3 weeks of the study and were not significantly modified by probucol treatment.…”
Section: Resultsmentioning
confidence: 68%
“…Obese mice were also hyperglycaemic and hyperinsulinaemic as compared with lean mice (Fig. 1c and Table 2) [31]. All these parameters remained rather stable throughout the 3 weeks of the study and were not significantly modified by probucol treatment.…”
Section: Resultsmentioning
confidence: 68%
“…In our present study long-term DADLE treatment produced a significant (P<0.05) hyperglycemia in the experimental group. This increasing effect of DADLE on plasma glucose level may be due to its interaction with delta opioid receptors as suggested before [40][41][42] .…”
Section: Discussionmentioning
confidence: 95%
“…Bailey and Flatt [42] reported that mu receptor agonist DAMGO (D-Ala -ol-Enkephalin) and delta receptor agonist DADLE dose dependently increased plasma glucose levels in rats. Beta endorphin, which exhibits high affinity for delta opioid receptors [46] , has been found to significantly increase plasma glucose level [47] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, centrally administered opioids stimulate sympathetic outflow and produce hyperglycemia in nondiabetic rats (3) and dogs (2). Exogenously administered opioids can increase plasma glucose in the Aston strain of obese mouse (22], and naloxone reduces stress-induced hyperglycemia in nondiabetic BALB/c mice (23). Coupled with reports of increased levels of betaendorphin in pituitary tissue (20) and plasma of obese mice (5), and in patients with NIDDM (6, 7), these findings have given rise to the speculation that opioids could stimulate and contribute to hyperglycemia in some forms of diabetes.…”
Section: Effect Of Naltrexone On Insulin Responses To Epinephrine 2-mmentioning
confidence: 99%